Healers in the night - Rosny, Éric de (Orbis Books, 1985)
A Jesuit missionary teacher in Cameroon, who admits that from childhood he longed to immerse himself in another culture, tells the story of his quest to understand another religion, eventually undergoing initiation as a healer.
free
Keywords: Duala (African people) – Folklore